Extreme sensitivity of the northeastern Gulf of Lion (western Mediterranean) to subsurface heatwaves: physical processes and insights into effects on gorgonian populations in the summer of 2022 - C. Estournel; T. Estaque; C. Ulses; Q.-B. Barral; P. Marsaleix (Ocean Science)
In the summer of 2022, atmospheric conditions characterized by persistent anticyclonic anomalies caused an extreme marine heatwave in the western Mediterranean Sea. Time series of temperature profiles at various points along the northeastern coast of the Gulf of Lion (NW Mediterranean Sea) showed exceptional temperatures down to depths of 30 m, which led to massive mortality of benthic species. A hydrodynamic numerical simulation was used to analyze the physical processes responsible for this subsurface heatwave in a region where the climatology in summer is characterized by northerly winds inducing upwelling alternating with low winds. Firstly, the recurrence of heatwaves limited to the surface was demonstrated, triggered when upwelling stopped and warm water from the Northern Current intruded onto the shelf. More importantly, in August and early September 2022, two episodes of southerly and easterly winds of 8 to 10 m s−1 occurred. The oceanic response to these winds was an alongshore cyclonic current advecting warm water onto the shelf and a downwelling of this warm water to depths of the order of 30 to 40 m. A large part of the Gulf of Lion coast was warmed by these events. However, the northeastern part of the shelf, on either side of the city of Marseille, was by far the area most affected at depth due to the combination of the proximity of the warm surface waters of the Ligurian coast advected by wind-induced currents and the local acceleration of the wind by the continental topography, which intensifies the downwelling of these surface waters. These events are rare in summer, but their impact on the rich benthic ecosystems that characterize the region is dramatic and will only increase with the warming trend in surface waters, which is already close to 1 °C, as seen over the last decade.